1983
DOI: 10.1111/j.1600-0528.1983.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of root caries in the adult Finnish population

Abstract: A sample of 8000 persons was drawn to represent the Finnish population aged 30 years and over. The participation rate was 89.9%. Root caries was recorded when the lesion was obviously soft and more than half of it was located on cementum. Lesions adjacent to fillings were not included. The reproducibility and the standard of the clinical recordings were tested by reexamining 20% of the studied population 2-6 months after the first clinical examination. The overall prevalence of root caries was 21.6% for men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 6 publications
2
31
0
3
Order By: Relevance
“…Most of the recent epidemiological studies have reported gender-related differences in the prevalence of root caries, which has been higher in the men than in women [Vehkalahti et al, 1983;Papas et al, 1992;Fejerskov et al, 1993]. In our study population, as well, mean numbers of DRS, DFRS, and number of teeth with root caries were higher in men.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Most of the recent epidemiological studies have reported gender-related differences in the prevalence of root caries, which has been higher in the men than in women [Vehkalahti et al, 1983;Papas et al, 1992;Fejerskov et al, 1993]. In our study population, as well, mean numbers of DRS, DFRS, and number of teeth with root caries were higher in men.…”
Section: Discussionsupporting
confidence: 46%
“…In our study population, as well, mean numbers of DRS, DFRS, and number of teeth with root caries were higher in men. According to previous studies, age has a significant influence on the occurrence of root caries [Vehkalahti et al, 1983], which was also seen among the present study population.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Wearing partial dentures [Drake and Beck, 1993;Hellyer et al, 1990], the presence of calculus [Kerr. 1990], and the number of remaining teeth at risk, which may either be an indication o f an individual's good dental health or limited access to dental care [Vehkalahti et al. 1982;Kitamura et al, 1986;Beck ct al., 1988;Pure and Zickert, 1990;Joshi et al, 1993Joshi et al, ,1994, are some of the many factors involved in determining the root caries attack pat terns.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern o f occurrence was similar for both races with root surface disease being concentrated in the approximal surfaces of the anterior teeth in a small proportion of affected individuals, with whites presenting more tilled root increments than blacks. These findings suggest a need for more caries treatment in blacks and increased monitoring of this population since they are at a higher risk for root caries.When undertaking epidemiologic studies o f root caries among older adults, the number of remaining teeth and sur faces at risk (i.e., exposed) in a subject must be considered, since the pattern of tooth mortality among the elderly can affect the intraoral distribution of root caries [Vehkalahti et al" 1982;Kitamura et al, 1986; Beck et al" 1988; Fure and …”
mentioning
confidence: 99%